MENGURAI MAKNA CIVIL RELIGION PANCASILA SEBAGAI MORAL PUBLIK INDONESIA - Arief Firdaus (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Civil Religion terminology which was popularized by Robert N Bellah, a sociologist from the United States through his writing